A metodologia LMS para modelagem matemática de cartas de referência de valores dinamométricos para avaliação de membros superiores - Trotta, Juliano de (2016)
The Musculoskeletal Diseases related to work (WRMD) are the pathologies that require attention of companies in the industrial sector due to high incidence of absenteeism and the prevalence in through INSS, and the upper limbs the most affected body part. The measurement of muscular strength by grip strength is one of the methods to measure the functional capacity a person, but international tables dynamometric values that are used as normal parameters are conflicting with the population of the Brazilian industrial sector. In this context, we see the need to create a specific standards model for the electromechanical industry sector to assist occupational medicine to check the capability to execute a labor activity, preventing from DORT. The aim of this study is to develop normal values for palmar grip strength and scapular tests by percentile cards method that met the Brazilian population in the industrial sector, correlating to the variables: age, gender and hand dominance, to provide support in the fitness professional decision. A retrospective, descriptive cross-sectional study was made with 2902 healthy employees between 16 and 63 years from database of electromechanical companies of the Curitiba metropolitan area. The data was analyzed using descriptive statistics with position and dispersion measurements and reference cards have been elaborated from the LMS method (Least Median Square), where L is transformation "BoxCox", M is median and S is coefficient of variation. The results showed that the median grip dinamometric of this research are below international studies and that percentílicas curves formed by the values of dinamometrias this sample have a progressive value with age. This methodology for the male gender allowed the formatting charts that show normal ranges according to each age. It was concluded that the dynamometric values grip and scapular found today in the international literature are contradictory when applied to the population of the national electromechanical industry. Percentile cards method related to age and gender, it was possible to format a mathematical modeling with normal graphics, easy usage, when related to the degree of ergonomic risk of working location aids medical thinking as the ability to take a certain labor activity. As a future proposal, it is suggested to continue their studies with the same methodology for the female gender and the association of other technological methods sensitive to the detection and prevention of osteoarticular diseases related or not with work, as thermography.